Efectividad de los antioxidantes en el aceite de girasol - Carelli Albarracin, Amalia Antonia (2000)
Lipid oxidation affects the quality and deterioration of refined sunflower oil. Fatty acid composition, oxygen, antioxidant content, light, temperature, and the presence of metals are among the factors that influence the degree of oil stability.The purpose of this study is based on the effectiveness of the various antioxidants added to sunflower oil and the assessment of their real action through different laboratory methods.